2006
DOI: 10.1159/000096089
|View full text |Cite
|
Sign up to set email alerts
|

Mutation and Polymorphism Analyses of <i>INSL3</i> and <i>LGR8</i>/<i>GREAT</i> in 62 Japanese Patients with Cryptorchidism

Abstract: Background/Aims: Although insulin-like factor 3 (INSL3) and its receptor leucine-rich repeat-containing G protein-coupled receptor 8/G protein-coupled receptor affecting testis descent (LGR8/GREAT) are essential for the gubernacular development, mutations of INSL3 and LGR8/GREAT are infrequent in patients with cryptorchidism (CO), and there is no report documenting a positive association of CO with a polymorphism in INSL3 or LGR8/GREAT. Here, we further examined the relevance of INSL3 and LGR8/GREAT mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…The role of this peptide in the control of testis descent in humans is less clear cut. Mutational analysis of the INSL3 and LGR8/GREAT genes in boys with either unilateral or bilateral cryptorchidism has revealed only a small minority of cases that harbour sequence changes of functional significance (24). A number of substitutions are reported such as Ala60Thr in INSL3 and Ile160Val in LGR8, but functional studies in vitro show no ligand or receptor dysfunction.…”
Section: Transabdominal Phasementioning
confidence: 99%
“…The role of this peptide in the control of testis descent in humans is less clear cut. Mutational analysis of the INSL3 and LGR8/GREAT genes in boys with either unilateral or bilateral cryptorchidism has revealed only a small minority of cases that harbour sequence changes of functional significance (24). A number of substitutions are reported such as Ala60Thr in INSL3 and Ile160Val in LGR8, but functional studies in vitro show no ligand or receptor dysfunction.…”
Section: Transabdominal Phasementioning
confidence: 99%
“…Foresta et al [2008] recently reviewed the published data on the INSL3 and LGR8 genes regarding cryptorchidism development. Mutations in these 2 loci have been analyzed in 15 and 7 studies, respectively, including more than 1,500 and almost 1,000 patients with cryptorchidism, respectively, and similar numbers of controls [Koskimies et al, 2000;Krausz et al, 2000;Tomboc et al, 2000;Lim et al, 2001;Marin et al, 2001a, b;Takahashi et al, 2001;Baker et al, 2002;Gorlov et al, 2002;Canto et al, 2003;Ferlin et al, 2003Ferlin et al, , 2006Roh et al, 2003;Feng et al, 2004;Foresta and Ferlin, 2004;Bogatcheva et al, 2007;El Houate et al, 2007;Yamazawa et al, 2007]. Some mutations have been found in both controls and patients and are therefore considered as normal variants, whereas other mutations are detected only in cases [Foresta et al, 2008].…”
Section: Insulin-like Factor 3 and Lgr8 Genesmentioning
confidence: 99%
“…For SNP genotyping by PCR-RFLP, 17 μl of purified DNA, 2 μl of buffer and 1 μl of the restriction enzyme were incubated for [18][19][20] h. The restriction enzymes used for SNP #5 and #6 were BsmAI (5,000 U/ml, New England BioLabs, Beverly, MA, USA) and MboI (10,000 U/ml, Takara Bio, Otsu, Shiga, Japan), respectively.…”
Section: Pcr-rflpmentioning
confidence: 99%
“…In humans, several candidate genes including androgen receptor (AR) gene [10][11][12], estrogen receptor (ER) gene [13][14][15], insulinlike peptide 3 (INSL3) gene and INSL3 receptor (LGR8) gene [12,[16][17][18] have been investigated for CO. Using single nucleotide polymorphism (SNP) genotyping, which is one of the recent molecular approaches applied to identify candidate genes [19], Yoshida et al [13] reported the association of a specific haplotype (AGATA) including 5 SNPs in the 3' end of the ERα gene (ESR1) with CO in humans.…”
mentioning
confidence: 99%